2022
DOI: 10.1111/acel.13696
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord plasma concentrate has beneficial effects on DNA methylation GrimAge and human clinical biomarkers

Abstract: Plasma transfusions are standard treatments to replace missing proteins in people with rare genetic diseases. Prior studies have demonstrated that heterochronic parabiosis has beneficial effects on several tissues of old animals receiving young blood. Human clinical trials are currently underway to investigate whether the infusion of plasma or plasma‐derived factors from young donors can be used to mitigate human age‐related conditions. Here, we use data from a safety study (n = 18, mean age 74) to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…Another promising strategy for improving healthspan in elderly individiduals seems to be treatment with human umbilical cord plasma concentrates (HUCPC). Thus, in a phase 1 trial, it has been recently reported that intramuscular administration of HUCPC for 10 weeks to a group of 18 elderly subjects (average age, 74) improved the levels of different biomarkers, including epigenetic age measures, a number of clinical biomarkers of organ dysfunction, mitochondrial DNA copy number and leukocyte telomere length (32). The study also reports that umbilical cord blood plasma rejuvenates the kidney and leads to moderate epigenetic rejuvenation in human blood.…”
Section: Discussionmentioning
confidence: 99%
“…Another promising strategy for improving healthspan in elderly individiduals seems to be treatment with human umbilical cord plasma concentrates (HUCPC). Thus, in a phase 1 trial, it has been recently reported that intramuscular administration of HUCPC for 10 weeks to a group of 18 elderly subjects (average age, 74) improved the levels of different biomarkers, including epigenetic age measures, a number of clinical biomarkers of organ dysfunction, mitochondrial DNA copy number and leukocyte telomere length (32). The study also reports that umbilical cord blood plasma rejuvenates the kidney and leads to moderate epigenetic rejuvenation in human blood.…”
Section: Discussionmentioning
confidence: 99%
“…For a complete overview of enriched GO-, KEGG-and Reactome terms within each cluster, see Supplementary Table S5. injected with human umbilical cord plasma showed that this approach is safe and beneficially altered multiple biomarkers (Clement et al, 2022). These results highlight that factors present in aged blood promote aging and that modulating the blood composition can be a therapeutic option to promote healthy aging in humans.…”
Section: Figurementioning
confidence: 70%
“…As these two organs are involved in filtering the blood, it may be that due to the aging process these organs cannot properly function anymore, leading to a more toxic and less homeostatic environment in the blood over time. A recent study using umbilical cord plasma injections in human elderly showed beneficial effects on estimated ages using epigenetic profiles, but also improved biomarkers of kidney functioning such as creatinine levels and estimated glomerular filtration rates (Clement et al, 2022). Altogether, this points to an important role of these organs in aging and suggests impaired functioning of these organs over time.…”
Section: Discussionmentioning
confidence: 92%
“…Another promising strategy for improving healthspan in old individuals seems to be treatment with human umbilical cord plasma concentrates (HUCPC). Thus, it has been recently reported that intramuscular administration of HUCPC for 10 weeks to a group of 18 elderly subjects (average age, 74) improved the levels of different biomarkers, including epigenetic age measures, a number of clinical biomarkers of organ dysfunction, mitochondrial DNA copy number, and leukocyte telomere length ( 32 ).…”
Section: Discussionmentioning
confidence: 99%